Manajemen Evaluasi Keberhasilan Pelaksanaan Bimbingan Belajar di SMAN 1 Parigi - Aidah Fitri Robi'ah Aziz; Irma Nurohmah; Azlika Avilla Mutia; Hilman Farid (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2024)
This research aims to describe the evaluation management of the success of implementing tutoring at SMAN 1 Parigi by focusing on the role of guidance and counseling teachers in supporting academic achievement and student development. The research method used in this research is a qualitative approach with descriptive methods. The research results show that the management of evaluating the success of implementing tutoring at SMAN 1 Parigi is carried out by subject teachers and homeroom teachers. Tutoring is provided with an academic focus, with an emphasis on effective time management and appropriate study methods. In terms of managing the evaluation of the success of tutoring, guidance and counseling teachers rely on student report cards from UTS/UAS, as well as certificates from extracurricular activities. The main obstacle faced is students' low learning motivation, which is influenced by environmental factors, peers, lack of family support, and less interesting learning methods. Counseling teachers act as motivators, good listeners, and givers of advice to overcome student problems. Even though guidance and counseling teachers try to implement positive discipline, physical punishment has been replaced by memorizing surahs, lesson materials, or reciting prayers. However, challenges arise when only a small percentage of students show positive changes, while others continue to face behavioral and academic problems. This is related to the student's character and lack of family support. This research provides in-depth insight into the management of guidance and counseling in high schools, especially at SMAN 1 Parigi, and highlights the critical role of guidance and counseling teachers in helping students achieve academic achievement and overcome social challenges.